Healthy eating decisions require efficient dietary self-control in children: A mouse-tracking food decision study. (1st October 2016) - Ha, Oh-Ryeong; Bruce, Amanda S.; Pruitt, Stephen W.; Cherry, J. Bradley C.; Smith, T. Ryan; Burkart, Dominic; Bruce, Jared M.; Lim, Seung-Lark
Abstract: Learning how to make healthy eating decisions, (i.e., resisting unhealthy foods and consuming healthy foods), enhances physical development and reduces health risks in children. Although healthy eating decisions are known to be challenging for children, the mechanisms of children's food choice processes are not fully understood. The present study recorded mouse movement trajectories while eighteen children aged 8–13 years were choosing between eating and rejecting foods. Children were inclined to choose to eat rather than to reject foods, and preferred unhealthy foods over healthy foods, implying that rejecting unhealthy foods could be a demanding choice. When children rejected unhealthy foods, mouse trajectories were characterized by large curvature toward an eating choice in the beginning, late decision shifting time toward a rejecting choice, and slowed response times. These results suggested that children exercised greater cognitive efforts with longer decision times to resist unhealthy foods, providing evidence that children require dietary self-control to make healthy eating-decisions by resisting the temptation of unhealthy foods. Developmentally, older children attempted to exercise greater cognitive efforts for consuming healthy foods than younger children, suggesting that development of dietary self-control contributes to healthy eating-decisions. The study also documents that healthy weight children with higher BMIs were more likely to choose to reject healthy foods. Overall, findings have important implications for how children make healthy eating choices and the role of dietary self-control in eating decisions.